2022
DOI: 10.3389/fnut.2022.1040089
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity as a risk factor of sarcopenic obesity in older adults

Abstract: Sarcopenic obesity is characterized by the loss of muscle strength, mass and muscle functionality and increased adipose tissue (obesity) according to different criteria and cut-off points. The prevalence of sarcopenic obesity among older adults is growing worldwide, and many factors are involved in its development. Diet and food security have been described as the main contributors to the development of obesity and sarcopenia. Food insecurity consists of limited or uncertain access to adequate and nutritious f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…However, such differences were not observed in men, indicating that elderly women with sarcopenic obesity exhibited the worst dietary characteristics, making them particularly vulnerable to healthy diets. Food insecurity increases the likelihood of obesity and sarcopenia in the elderly [ 4 ]. Therefore, improving food insecurity could be a strategy for reducing the risk of sarcopenic obesity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, such differences were not observed in men, indicating that elderly women with sarcopenic obesity exhibited the worst dietary characteristics, making them particularly vulnerable to healthy diets. Food insecurity increases the likelihood of obesity and sarcopenia in the elderly [ 4 ]. Therefore, improving food insecurity could be a strategy for reducing the risk of sarcopenic obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving food insecurity could be a strategy for reducing the risk of sarcopenic obesity. Additionally, the impact of food insecurity on obesity status differs by sex, as there was no association between food insecurity and obesity in elderly men [ 4 ]. Consequently, food insecurity is thought to have a more detrimental effect on women than on men among the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that food insecurity and malnutrition are significantly related to obesity and sarcopenia. [ 15 , 16 ] Especially in low- and middle-income countries, the incidence rate of the 2 syndromes is rising sharply among older people. [ 17 , 18 ] Adequate nutrition can effectively reduce muscle loss and improve the quality of life of older adults.…”
Section: Introductionmentioning
confidence: 99%